Analysis of Radome Cross Section of an Aircraft Equipped With a FSS Radome - Shin, Hokeun; Yoon, Daeyeong; Na, Dong Yeop; Park, Yong Bae (IEEE Access, 2022)
We study the radar cross section (RCS) property of an aircraft considering the electromagnetic (EM) characteristics of a frequency selective surface (FSS) radome, mounted on the aircraft. Instead of full-wave methods, we utilize high-frequency methods, such as the shooting and bouncing rays (SBR), physical theory of diffraction (PTD), and flat model, taking a significant computational efficiency. Based on the developed algorithm, we analyze monostatic and bistatic RCSs of the aircraft equipped with either single- and multi-layer dielectric, FSS, or PEC radomes in terms of frequency and polarization. Our calculations are validated by comparing with those of the commercial EM simulator with significant computational efficiency. The present numerical study indicates that including the radome EM characteristics into the overall aircraft RCS study is crucial for the accurate RCS estimate
Keywords: Flat model; Frequency selective surface; Frequency selective surface radome; Frequency-selective surfaces; Physical theory of diffraction; Radar cross section; Radar cross-sections; Shooting and bouncing ray; Shooting and bouncing rays; flat model; Frequency selective surface (FSS); FSS radome; physical theory of diffraction (PTD); radar cross section (RCS); shooting and bouncing rays (SBR)